Reserve Accumulation and International Monetary Stability. (Policy Papers; Policy Paper, 2010)
Since its last report to the IMFC in October 2009, the IEO has completed its evaluation report on IMF Interactions with Member Countries and finalized issues papers for evaluations on the IMF Performance in the Run-up to the Current Financial and Economic Crisis and Research at the IMF: Relevance and Utilization. On February 1, Moises Schwartz assumed his duties as the third Director of the IEO.